EL HALLAZGO DE UN QUIPUCAMAYOC EN CERRO COLORADO, HUACHO - Dalen Luna, Pieter D. van (2017)
We present the results of the analysis of a quipu recovered from the interior of an infant’s funeral bundle. This personage would have been a quipucamayoc, who in its growth would learn the office of accounting administrator in this quipu, that does not present any knot.